The Influence Of Profitability, Company Growth, And Previous Audit Opinions On Going Concern Audit Opinions : Case Study of JII70 Company on the Indonesian Stock Exchange 2018 -2021 - Sabri; Debi Sylvia; Zulhelmi (Gudang Jurnal Multidisiplin Ilmu, 2024)
This research aims to obtain empirical evidence about the influence of Profitability, Company Growth and Previous Year Audit Opinions on the acceptance of Going Concern Audit Opinions . The independent variables used are Profitability, Company Growth and Previous Year Audit Opinion. And the dependent variable used is Going Concern Audit Opinion . This type of research data is secondary data obtained from www.idx.co.id and the company website. This research uses a purposive sampling method with the sample companies in this research being the Jakarta Islamic Index 70 (JII70) companies listed on the Indonesia Stock Exchange in 2018-2021. The number of samples obtained was 28 companies with observations for 4 years. The hypothesis in this study was tested using logistic regression analysis using SPSS version 26. The results of this study based on a partial test (Wald test) showed that: 1) The Profitability variable had no significant effect on the Going Concern Audit Opinion . 2) The Company Growth variable has no significant effect on the Going Concern Audit Opinion . 3) The previous year's Audit Opinion variable has a significant effect on the Going Concern Audit Opinion . And based on the results of the simultaneous test (omnibus test) it shows that the variables Profitability, Company Growth and Previous Year Audit Opinion simultaneously have a significant effect on the Going Concern Audit Opinion . And the determinant coefficient obtained was 0.390 or 39%, which means that the independent variable contributed 39% to the dependent variable and the remaining 61% was explained by other variables outside this research.